Legal Writing and Ascertainment of Causation in the Italian Judiciary Process - Grandi, Barbara (Archives of Business Research, 2023)
There is an ongoing debate about methods of legal writing in Italy, and particularly about requirements the legislator should adopt to make the law as clearer as possible, that is to say, to avoid, as much as it is possible, that the law itself contributes to its own misunderstanding, to its own wrong application by way of permitting diverging interpretations. The practice of giving a list of ‘consideranda’ before the adoption of any normative act expresses a democratic reply to the issue (derived from the European model) for any citizen’s to understand motivations of the legislator directives, beyond the content of directive itself.